Development of an Index to Evaluate the Environmental Performance of Sugar-Energy Production Plants - Rebelato, Marcelo Girotto [UNESP]; Rodrigues, Andreia Marize [UNESP]; Saran, Luciana Maria [UNESP]; Madaleno, Leonardo Lucas; de Oliveira, Otávio José [UNESP] (Springer Nature, 2020)
Few studies address how to measure the impacts of the sugar-energy industry on the environment and human health. Thus, in this paper, an index (Iepa) to evaluate the impacts of the sugar-energy manufacturing process on the well-being of ecosystems and human society is proposed. The proposed index was developed from: (1) the environmental impact potential of each waste/by-product; (2) the relative weighting of its impact potential; (3) the relative amount of the waste/by-product produced over a given period of time; (4) the relative geographic coverage (spatial dispersion) of each waste/by-product; and (4) the appropriateness of the disposal of each waste/by-product generated. For validation, the index was used to evaluate the environmental performance of a large Brazilian sugar and ethanol company. It was determined that vinasse accounted for more than half of the relative mass of the waste/by-products generated by the company and that it contributed significantly (93.23%) to the Iepa value. The final Iepa value was 73.73%, which means that the disposal of 73.73% of the waste/by-products generated by the company was determined to be “environmentally adequate.” The waste whose disposal was assessed to be “inadequate” consisted of the gases from the bagasse burning and those produced in the fermentation process. The latter accounted for only 1.3% of the total emissions, while the former accounted for 20% of the total emissions. CO2 was the main constituent of both types of waste. However, it should be noted that sugarcane is a renewable form of energy that captures more CO2 from the atmosphere than any other crop.
Keywords: Environment index; Environmental impact potential; Environmental indicators; Ethanol industry; Sugar-energy industry; Waste generation